Are they still determining? Analysis of associations among ethnicity, gender, socioeconomic status, neighborhood factors, and COVID-19 vaccination - Kim, Bokyung; Hong, Seoyeon; Kim, Sungwook (Frontiers in Communication, 2023)
This study explores associations among adult vaccination, ethnicity, gender, socioeconomic variables such as education attainment and income, as well as neighborhood factors in a telephone quota sample of New Jersey adults (N=1,984). Our multivariate logistic regression analyses found that certain race/ethnicity, respondents’ household income, and perceived safety of one’s community, were the strongest predictors of COVID-19 vaccination. The odds of COVID-19 vaccination were lower for Black/African American respondents by 52% compared to White/Caucasian respondents (p =0.001), and 44% lower for Hispanic/Latino respondents compared to White/Caucasian respondents (p = 0.001). The results add new insights to public health communication research and suggest careful interventions across racial groups, considering existing racial disparities in vaccination.